Female Adnexal Tumors of Probable Wolffian Origin with a Biphasic Histologic Growth Pattern and Positive for C-kit - Wei Zhang; Philip T. Valente; Nicole D. Riddle (Elsevier, 2016)
Female Adnexal Tumor of Probable Wolffian Origin (FATWO) is believed to be derived from the mesonephric (Wolffian) remnants commonly located in the broad ligament. Here we report a case of FATWO with unique histologic growth pattern. The tumor has a solid growth pattern with both epithelioid and spindle cell components. Immunohistochemistry (IHC) showed tumor cells to be diffusely positive for Estrogen receptor (ER) and Progesterone receptor (PR). The epithelioid areas were positive for AE1/3, CK-7 and CAM 5.2. The spindle cell areas were positive for Vimentin and CD10. The tumor cells were negative for Inhibin, CK20, P53, CA125, CD99, Calretenin and CK5/6. Interestingly, the tumor cells are positive for C-kit, which provides additional evidence for possible therapy using tyrosine kinase inhibitors (TKI). However, the frequency of c-kit expression in this tumor and its relevance to therapeutic efficacy using TKI for the recurrent and metastatic tumor are unknown and merit further study.